Food additives data book - Smith, Jim, 1953-; Hong-Shum, Lily (Blackwell Science, 2003)
This major new reference work covers all the "must-have" technical data on food additives. Compiled by food industry experts with a proven track record of producing high quality reference work, this volume is the definitive resource for technologists in small, medium and large companies, and for workers in research, government and academicinstitutions. Coverage is of Preservatives, Enzymes, Gases, Nutritive additives, Emulsifiers, Flour additives, Acidulants, Sequestrants, Antioxidants, Flavour enhancers, Colour, Sweeteners, Polysaccharides, Solvents. Entries include information on: Function and Applications, Safety issues, International legal issues, Alternatives, Synonyms, Molecular Formula and mass, Alternative forms, Appearance, Boiling, melting, and flash points, density, purity, water content, solubility, Synergists, Antagonists, and more with full and easy-to-follow-up references.